1996
DOI: 10.2116/analsci.12.835
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis of Cationic Polyacrylamide Resins by Reactive Pyrolysis-Gas Chromatography in the Presence of Organic Alkali

Abstract: Reactive pyrolysis-gas chromatography (Py-GC) in the presence of tetramethylammonium hydroxide (TMAH) was successfully applied to the compositional analysis of cationic polyacrylamide (PAAm) resins, prepared from acrylamide (AAm) and dimethylaminoethylmethacrylate (DM). The reactive pyrolysis of cationic PAAm resulted only in hydrolysis of ester linkages in DM units and did not lead to subsequent methylation of hydrolyzates and cyclization. The intense peak of 2-(dimethylamino)ethanol formed from DM units thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Reactive Py-GC Conditions. Basically the same measuring system for reactive Py-GC described in our previous papers [30][31][32][33][34][35] was used in this system. A vertical microfurnace pyrolyzer (Frontier Lab, PY-2010D) was attached to a gas chromatograph (Shimadzu GC-17A) equipped with a flame ionization detector (FID).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive Py-GC Conditions. Basically the same measuring system for reactive Py-GC described in our previous papers [30][31][32][33][34][35] was used in this system. A vertical microfurnace pyrolyzer (Frontier Lab, PY-2010D) was attached to a gas chromatograph (Shimadzu GC-17A) equipped with a flame ionization detector (FID).…”
Section: Methodsmentioning
confidence: 99%
“…Here, reactive Py-GC in the presence of some specific reagents might provide a key to solve this problem. It has been shown that reactive Py-GC of condensation polymers in the presence of an organic alkali such as tetramethylammonium hydroxide (TMAH) results in a simplified pyrogram which consists of characteristic peaks of methyl derivatives reflecting the components of the original polymers. , This technique has successfully been applied to structural characterization of various synthetic polymers, rosin sizing agent in paper, and lipids in zooplanktons . Another reactive pyrolysis in the presence of inorganic solid acids such as cobalt sulfate has been successfully applied to the sequential analyses of copolymer polyacetals .…”
mentioning
confidence: 99%